2009
DOI: 10.1175/2008jcli2527.1
|View full text |Cite
|
Sign up to set email alerts
|

Why the Western Pacific Subtropical High Has Extended Westward since the Late 1970s

Abstract: The western Pacific subtropical high (WPSH) is closely related to Asian climate. Previous examination of changes in the WPSH found a westward extension since the late 1970s, which has contributed to the interdecadal transition of East Asian climate. The reason for the westward extension is unknown, however. The present study suggests that this significant change of WPSH is partly due to the atmosphere's response to the observed Indian Ocean-western Pacific (IWP) warming. Coordinated by a European Union's Sixth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
312
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 498 publications
(341 citation statements)
references
References 61 publications
23
312
0
6
Order By: Relevance
“…The results indicate that diabatic heating plays a reinforcing role in the westward and intensified WNPSH, which are consistent with some previous studies (Zhou et al 2009;Matsumura et al 2015). However, some studies have found the WNPSH bias is also related to other bias in BCC_AGCM2.2, such as the wet bias over the Indian summer monsoon region, weak walker circulation, and lower air temperature over the Tibetan Plateau Kan et al 2015).…”
Section: Summary and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results indicate that diabatic heating plays a reinforcing role in the westward and intensified WNPSH, which are consistent with some previous studies (Zhou et al 2009;Matsumura et al 2015). However, some studies have found the WNPSH bias is also related to other bias in BCC_AGCM2.2, such as the wet bias over the Indian summer monsoon region, weak walker circulation, and lower air temperature over the Tibetan Plateau Kan et al 2015).…”
Section: Summary and Discussionsupporting
confidence: 91%
“…Next we carry out further analysis to understand the bias in simulated WNPSH. It is believed that diabatic heating associated with the Asian summer monsoon rainfall affects the summer subtropical circulation over the North Pacific (Rodwell and Hoskins 2001;Zhou et al 2009). Figure 11 shows the model bias in vertical integrated diabatic heating (shaded) from the surface to 200 and 850 hPa non-divergent flow (vector) for phase 1 and 5.…”
Section: Intra-seasonal Variability Of the Western North Pacific Subtmentioning
confidence: 99%
“…In fact previous studies using AGCM experiments driven by recent basin-wide warming in the tropical Indian Ocean reproduced the observed zonal wind changes in the recent decades 38 . In the model sensitivity experiment, however, the positive SST offset is prescribed only over the western Indian Ocean region, where the long-term warming trend is observed in the SST records during 1901-2012.…”
Section: Resultssupporting
confidence: 56%
“…4E,F with H). Such a pattern of opposing variability in monsoon rainfall over southern and northern China is well documented and characterizes observed and simulated precipitation trends over the latter half of the twentieth century, changes apparently related to shifts in tropical Pacific and Indian Ocean temperatures (see discussions in Li et al 2008;Zhou et al 2009). …”
Section: Proxy Recordsmentioning
confidence: 69%